2017
DOI: 10.3168/jds.2016-11221
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of calves fed microbially enhanced soy protein in pelleted starters

Abstract: Our objective was to determine effects of feeding calves pelleted starters with microbially enhanced (fungi-treated) soy protein (MSP) in replacement of soybean meal (SBM) with different milk replacers (MR). Thirty-six Holstein calves (2 d old; 24 females, 12 males) in individual hutches were used in a 12-wk randomized complete block design study. Treatments were (1) MSP pellets with MR formulated for accelerated growth (28% crude protein, 18% fat; MSPA), (2) SBM pellets with MR formulated for accelerated grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
(38 reference statements)
5
12
1
Order By: Relevance
“…Similar levels of plasma glucose among the treatments in our study indicated that calves were similar in energy status across diets (Senevirathne et al, 2017). As calves age, the concentration of plasma BHB increases, mainly due to an increase in starter feed intake and consequent rumen development (Nemati et al, 2015).…”
Section: Blood Metabolites and Rumen Phsupporting
confidence: 62%
“…Similar levels of plasma glucose among the treatments in our study indicated that calves were similar in energy status across diets (Senevirathne et al, 2017). As calves age, the concentration of plasma BHB increases, mainly due to an increase in starter feed intake and consequent rumen development (Nemati et al, 2015).…”
Section: Blood Metabolites and Rumen Phsupporting
confidence: 62%
“…Body length was greater (P < 0.01) in calves fed RW than MW in the second week and then comparable throughout the rest of the study (data not shown), which resulted in tendency for a treatment by week interaction (P = 0.08) with calves fed RW having 0.65 cm greater body length than calves fed MW. Overall, BCS were similar between treatments (Table 5) and BW, ADG, and frame growth measurements were comparable to research conducted with calves on similar diets and during a similar period of age (Stamey et al, 2012;Senevirathne et al, 2017).…”
Section: Body Frame Growthsupporting
confidence: 75%
“…Both treatment groups showed slow increases in starter intake preweaning and a rapid increase in starter intake was observed during the postweaning period. Similarly, a slow increase in starter intake during the preweaning period and a rapid increase in starter intake during weaning has been demonstrated in other research (Khan et al, 2007;Senevirathne et al, 2017).…”
Section: Intakessupporting
confidence: 73%
See 2 more Smart Citations